The Role of Employee Welfare in Increasing Loyalty and Productivity - Ratih Aprilia Sari; Dita Wirahapsar; Edy Raharja (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Employee welfare is a crucial factor in forming a contribution to productivity and loyalty in the workplace environment. This study aims to explain the relationship between the formation of employee welfare and their level of productivity and loyalty. And the method used in this study is to use a survey involving 200 respondents from various industries. And there are research results obtained that have explained that there is a very significant positive relationship related to the relationship between employee welfare and loyalty and productivity. Which in this study has focused that investment in welfare programs can contribute to organizational performance.